Analysis of the Academic Information System (SIAKAD) Using Tyler’s Goal Oriented Evaluation Model - Oktira, Yona Syaida; Ambiyar, Ambiyar; Rizal, Fahmi (The Future of Education Journal, 2025)
This study aims to analyze the success of the Academic Information System (SIAKAD) at Nahdlatul Ulama University of West Sumatra (UNU Sumbar) in achieving its predetermined objectives. The study employs the Goal-Oriented Evaluation Model, first introduced by Robert E. Stake in 1967. Stake is a prominent educational evaluation scholar known for his goal-based evaluation approach, which is also discussed in Donna Mertens’ program evaluation framework. This research adopts a descriptive qualitative methodology to identify the primary objectives of the Academic Information System (SIAKAD) and to measure the extent to which these objectives have been achieved based on data collected from various stakeholders, including the Head of the Information Systems Unit at UNU Sumbar, lecturers, students, and institutional partners. Data were collected and analyzed through interviews, observations, and document analysis. The findings indicate that most of the primary objectives of the Academic Information System particularly improving administrative efficiency and data accuracy have been successfully achieved. However, several objectives related to user satisfaction, feature optimization, and system readiness in response to technological advancements still require further attention. Strategic recommendations are therefore proposed to enhance the sustainability of the Academic Information System (SIAKAD) at UNU Sumbar so that it can more effectively support the Tridharma of Higher Education within the university context.